ANALISIS PEMBELAJARAN BERDIFERENSIASI DALAM MATA PELAJARAN IPAS KELAS VI MATERI RANGKA, SENDI, DAN OTOT DI SDN 1 PAGAR AIR ACEH BESAR - Pira Nurhasanah; Mislinawati; Tursinawati (STKIP Subang, 2026)
Differentiated learning is an instructional approach that accommodates the diversity of students’ characteristics and learning needs in the classroom. However, each educational institution has different characteristics, making further analysis necessary to examine how differentiated learning is implemented at SDN 1 Pagar Air, Aceh Besar. This study aims to analyze the implementation of differentiated learning in the IPAS subject for Grade VI on the topic of the skeletal system, joints, and muscles at SDN 1 Pagar Air, Aceh Besar. This research employs a qualitative approach with a descriptive research design. The research subjects consist of the teacher and Grade VI students, while the focus of the study is on the planning and implementation of differentiated learning. Data were collected through classroom observations, teacher interviews, and analysis of instructional modules. The data were analyzed by examining and connecting findings from the three data sources to obtain a comprehensive description of instructional practices. The results of the study indicate that differentiated instruction was implemented beginning with the mapping of students’ characteristics, learning needs, and learning style tendencies, which served as the basis for developing instructional materials and selecting learning media. In practice, content differentiation was reflected in the use of varied learning media aligned with students’ learning styles, although the same learning material was still provided to all students. Process differentiation was implemented through the use of varied teaching methods, learning activities, and differentiated guidance based on students’ needs, while product differentiation was realized by allowing students to demonstrate their learning outcomes through different products while maintaining the same learning objectives. It can be concluded that the implementation of differentiated instruction reflects contextual teaching practices that accommodate student diversity and support the achievement of learning objectives.